ACVIM consensus statement: Guidelines for the identification, evaluation, and management of systemic hypertension in dogs and cats. (24th October 2018) - Acierno, Mark J.; Brown, Scott; Coleman, Amanda E.; Jepson, Rosanne E.; Papich, Mark; Stepien, Rebecca L.; Syme, Harriet M.
Abstract : An update to the 2007 American College of Veterinary Internal Medicine (ACVIM) consensus statement on the identification, evaluation, and management of systemic hypertension in dogs and cats was presented at the 2017 ACVIM Forum in National Harbor, MD. The updated consensus statement is presented here. The consensus statement aims to provide guidance on appropriate diagnosis and treatment of hypertension in dogs and cats.